Pseudoaneurysm of cavernosal artery presenting as priapism in a 7-year-old boy - Pavai Arunachalam; Elango Swamiappan; Mathew Cherian; Nitish Rajakamar Jayaharan (Wolters Kluwer Medknow Publications, 2021)
Priapism due to pseudoaneurysm of the cavernosal artery is very rare. Herein, we describe the magnetic resonance imaging and digital subtraction angiographic findings of pseudoaneurysm in the right corpus cavernosum in a 7-year-old boy who presented with pain in the penis and lower abdomen and priapism with an obscure history of trauma. This was managed by endovascular embolization of the aneurysm. One-year follow-up has shown him to be normal without any symptoms and normal erection.